2018
DOI: 10.3390/ma11050859
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Sorption Enhanced Steam Reforming (SESR) of Biomass in a Fluidised-Bed Reactor Using Combined Multifunctional Particles

Abstract: The performance of combined CO2-sorbent/catalyst particles for sorption enhanced steam reforming (SESR), prepared via a simple mechanical mixing protocol, was studied using a spout-fluidised bed reactor capable of continuous solid fuel (biomass) feeding. The influence of particle size (300–500 and 710–1000 µm), CaO loading (60–100 wt %), Ni-loading (10–40 wt %) and presence of dicalcium silicate support (22.6 wt %) on SESR process performance were investigated. The combined particles were characterised by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…solar photovoltaics and wind energy [1]. Current global H2 production is around 75 Mt per annum, of which 76% is produced from natural gas (205 Gm 3 , or 6% of current global natural gas use) and 23% from coal (107 Mt, or 2% of global coal use), however, its production contributes about 830 Mt CO2 emissions to the atmosphere per year (2% of global annual emissions) [1]. With the rapid growth rate in H2 demand, CO2 emissions from hydrogen production are predicted to increase significantly, if it is supplied from natural gas or coal without carbon capture and storage (CCS) technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…solar photovoltaics and wind energy [1]. Current global H2 production is around 75 Mt per annum, of which 76% is produced from natural gas (205 Gm 3 , or 6% of current global natural gas use) and 23% from coal (107 Mt, or 2% of global coal use), however, its production contributes about 830 Mt CO2 emissions to the atmosphere per year (2% of global annual emissions) [1]. With the rapid growth rate in H2 demand, CO2 emissions from hydrogen production are predicted to increase significantly, if it is supplied from natural gas or coal without carbon capture and storage (CCS) technologies.…”
Section: Introductionmentioning
confidence: 99%
“…One innovative option is sorption enhanced steam reforming (SE-SMR), which involves an in-situ CO2 capture process where the hydrocarbon fuel is reacted with steam in the presence of a CO2 sorbent and a reforming catalyst to generate decarbonised, high purity H2 [3]. The concept of SE-SMR is not new.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this critique the authors performed thermogravimetric tests in pure CO2 and demonstrated a higher performance of the CaO modified by polymorphic spacers in this case as well [403]. Other studies contradict these results, showing CaO modified with Ca2SiO4 to still show the typical decay of unmodified CaO [402], [413], clearly highlighting the need for more analysis of these materials.…”
Section: Nano-and Microstructured Morphologiesmentioning
confidence: 94%
“…CH4 [671]- [674], biomass [413], glycerol [448], [675]- [678] or ethanol [679]- [682]), to capture CO2 at a high efficiency for a long time, and possibly to enable redox-reactions simultaneously for a better heat integration [683]- [686]. Combining these functionalities in a single particle (bi-functional or tri-functional catalyst-sorbent [687]) would maximize the heat integration of the different sub-reactions, but the design of such multifunctional materials is challenging so that typically separated particle systems (i.e.…”
Section: Enabling Co2 Capture On An Industrial Scalementioning
confidence: 99%
“…Clough et al (2018) andBaidya and Cattolica (2015), Ni-CaO and Ni-CaO-Fe catalysts were used respectively. They performed regeneration by calcining the used catalysts under high temperature with air.…”
mentioning
confidence: 99%